(untitled) (International Journal of Studies in Nursing, 2025)
Background: The COVID-19 pandemic disrupted nursing education, leading to reduced clinical training opportunities for nursing students. In 2023, the first cohort of graduates who experienced these disruptions entered clinical practice, raising concerns about their preparedness and ability to cope with workplace challenges. This study explores the experiences of new nurses transitioning to clinical work in the post-pandemic era, focusing on their adaptation strategies and the role of clinical nursing educators. Aim: To investigate how newly graduated nurses, who had limited clinical training due to the pandemic, adapt to clinical practice. This study also examines how clinical nursing educators modify their teaching approaches to support these nurses. Subject and Methods: This qualitative study utilized focus group discussions with two participant groups: newly employed nurses (who completed their final-stage clinical internship in 2022–2023) and their clinical nursing educators. Data were collected through structured focus group interviews and analyzed using a thematic approach to identify key adaptation experiences and instructional modifications. Results: Findings indicate that new nurses struggle with technical skills, communication, and clinical decision-making due to reduced hands-on training. Many experience "reality shock" upon entering the workforce, with common concerns including fear of treating COVID-19 patients, difficulties in time management, and hesitancy in professional interactions. Strategies such as peer discussions, mentor guidance, and structured on-the-job training were found to be helpful. Clinical nursing educators emphasized the need for extended adaptation periods, additional technical training, and enhanced psychological support to address new nurses’ challenges. Conclusion: Post-pandemic nursing graduates require tailored support to bridge the gap between theoretical knowledge and clinical practice. Hospitals should implement structured mentoring programs, additional technical training, and psychological support mechanisms to facilitate smoother transitions. Future policies should focus on optimizing clinical education and workplace integration for nursing students.